Challenging the Practice of Hilah in Contract Engineering in Islamic Financial Institutions from the Perspective of Islamic Business Ethics - Ainul Yaqin (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2024)
This paper aims to criticize the practice of contract engineering with the hilah formula from the perspective of Islamic business ethics. Several fatwas from DSN MUI related to the contracts in Islamic financial institutions are analyzed with the principles of Islamic business ethics. From the results of the analysis, it was concluded that the practice of engineering contracts using hilah had been carried out excessively and was not in line with the principles of Islamic business ethics. Islamic business ethics should be the main parameter in business practices in Sharia financial institutions so that the goals of the Islamic economic system can be realized and can be felt by the wider community.